Physiological risk factors for cardiovascular disease in middle-aged (40-60 years) adults and their association with dietary intake, Northern Iran - Simin Mouodi; Seyed Reza Hosseini; Robert Graham Cumming; Ali Bijani; Haleh Esmaeili; Reza Ghadimi (Babol University of Medical Sciences, 2019)
Background: Considering the importance of healthy diet in the protection of cardiovascular diseases (CVD), this research aimed to assess the physiological risk factors for CVD in middle-aged adults and their association with dietary intake in the north of Iran. Methods: In this cross-sectional study conducted in the years 2016-2017 among the adults aged 40-60 years living in Amirkola, Babol, the participants´ physical activity, dietary intake, body mass index, fat mass, blood pressure, fasting blood glucose and serum lipid profile were reported. The International Physical Activity Questionnaire was used to assess physical activity and a structured 24-hour food-recall questionnaire was used to assess the participants´ dietary intake. Consumed foods and beverages on two separate days were analyzed and transcribed in 10 food groups (gram). Results: Two hundred and ninety-one persons (96.7%) had complete participation, 96.2% with at least one CVD risk factor and 75.9% had overweight or obesity; 33% with hypertension; 6.2% had high fasting blood glucose; 64.6% with hypercholesterolemia, 47.8% had hypertriglyceridemia, and 8.9% with low HDL. Mean daily intake values of carbohydrate, protein and fat were all higher than dietary reference intakes for adults. Physical activity less than 1500 MET-minutes per week was significantly associated with having three or more physiological risk factors for CVD [adjusted odds ratio: 2.04 (1.08-3.85)] (P=0.029). Conclusion: Most of the middle-aged adults in this region had at least one of the physiological risk factors for CVD and daily intakes of carbohydrate and protein were higher than dietary reference intakes (DRIs) for adults.